2020
DOI: 10.1186/s13567-020-00836-3
|View full text |Cite
|
Sign up to set email alerts
|

Construction of polycistronic baculovirus surface display vectors to express the PCV2 Cap(d41) protein and analysis of its immunogenicity in mice and swine

Abstract: To increase expression levels of the PCV2 Cap(d41) protein, novel baculovirus surface display vectors with multiple expression cassettes were constructed to create recombinant baculoviruses BacSC-Cap(d41), BacDD-2Cap(d41), BacDD-3Cap(d41), and BacDD-4Cap(d41). Our results reveal that the recombinant baculovirus BacDD-4Cap(d41) was able to express the highest levels of Cap(d41) protein. Optimum conditions for expressing the PCV2 Cap(d41) protein were determined, and our results show that 107 of Sf-9 infected wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Inflammatory cytokines are key regulators of the animal immune system in regulating innate and adaptive immune responses ( 69 ). IFN-γ is the main effector of cellular immunity, which can activate CD8+ T lymphocytes and macrophages to kill foreign pathogens or infected cells ( 25 ). Most commercial vaccines focused only on humoral responses, including antigen-specific or neutralizing antibody responses; however, failed to induce strong cellular immunity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Inflammatory cytokines are key regulators of the animal immune system in regulating innate and adaptive immune responses ( 69 ). IFN-γ is the main effector of cellular immunity, which can activate CD8+ T lymphocytes and macrophages to kill foreign pathogens or infected cells ( 25 ). Most commercial vaccines focused only on humoral responses, including antigen-specific or neutralizing antibody responses; however, failed to induce strong cellular immunity.…”
Section: Discussionmentioning
confidence: 99%
“…We named this strain PCV2 SC2020. We designed primers tCap -F1 and tCap -R1 to amplify the truncated tCap gene according to the research by Chen ( 25 ). The PCR product was purified and cloned into pUCm-T using T Vector Rapid Cloning Kit (Sangon Biotech, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the Cap protein is an important target in the design of a novel PCV2 vaccine using genetic engineering technology. Studies have shown that cytokines and multiple epitopes can enhance the immune effect of vaccines [12,13]. CD154 is a kind of II type transmembrane protein.…”
Section: Introductionmentioning
confidence: 99%